2020
DOI: 10.17157/mat.7.1.657
|View full text |Cite
|
Sign up to set email alerts
|

Structural vulnerabilities and healthcare services integration

Abstract: Home to one fifth of all people living with HIV, South Africa carries the world’s heaviest burden of this disease. While a significant proportion of those infected are immigrants from other African high-prevalence countries, little is known about how these migrants engage with healthcare systems in shifting cultural and clinical settings. This article draws on fieldwork from migrant communities and twenty-one ethnographic life histories told by HIV-positive Mozambicans in a major South African HIV clinic. From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Another small qualitative study that explored the experiences of eight women refugees and their attempts at utilising reproductive health care services in Durban's public sector also reported incidents of medical xenophobia [23]. A final small ethnographic study with 21 HIV positive Mozambicans found that their access to health care services was constrained due to structural vulnerabilities and HIV stigma [24].…”
Section: Introductionmentioning
confidence: 99%
“…Another small qualitative study that explored the experiences of eight women refugees and their attempts at utilising reproductive health care services in Durban's public sector also reported incidents of medical xenophobia [23]. A final small ethnographic study with 21 HIV positive Mozambicans found that their access to health care services was constrained due to structural vulnerabilities and HIV stigma [24].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, TB is still the biggest cause of death for people living with HIV in South Africa, and the rise of drug-resistant TB strains, which are more challenging and expensive to treat, has made the situation even worse. In order to expedite the start of antiretroviral therapy (ART) for PLHIV with TB, the Centers for Disease Control and Prevention (CDC) in South Africa, through its Global AIDS Program (GAP), is collaborating closely with the NDoH, much like with Covid-19, to strengthen HIV/TB screening for all persons living with HIV (PLHIV), including migrants [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the possible explanations could be that there is a gap in literature on barriers that prevent migrants from reporting their household member with HIV-positive status or engaging healthcare systems with such medical problems. Also, shifting cultural and clinical settings may result in structural vulnerabilities that are limiting immigrants’ household members with such medical history of HIV-positive status from accessing and having proper integration within healthcare services [ 80 , 81 ]. However, these barriers include stigmatization of HIV-positive household members, social seclusion, xenophobia and deportation, marginalization and mistreatment, language obstacles, ethnic hostility, and medical heterogeneity [ 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Important recent contributions seek measures for individual level mechanisms of stigma (internalized, enacted, and anticipated) (Earnshaw et al 2013) and chart stigma's "biosocial ambiance" of lonely silence and secrecy that is detrimental to the social normalization of HIV treatment-seeking (Steenberg 2020a). Structural vulnerabilities also limit integration within HIV/AIDS services, delay treatment-seeking, and inhibit drug adherence, especially for migrants, including: perilous migration, xenophobia and deportation, exclusion and exploitation, language barriers, medical pluralism, cultural estrangement, social isolation, and the stigmas of being HIV-positive (Steenberg 2020c).…”
Section: Precarity Stigma and Treatment-seekingmentioning
confidence: 99%